Further insights into anti-IgLON5 disease: a case with complex clinical presentation - Simone Pierro; Federico Verde; Alessio Maranzano; Anna De Gobbi; Eleonora Colombo; Alberto Doretti; Stefano Messina; Luca Maderna; Antonia Ratti; Floriano Girotti; Francesca Andreetta; Vincenzo Silani; et al. (BMC Neurology, 2024)
Abstract Background Anti-IgLON5 disease is an autoimmune encephalitis overlapping with neurodegenerative disorders due to pathological accumulation of hyperphosphorylated tau. It is characterized by several clinical manifestations determined by involvement of different brain areas, and mild response to first-line immunotherapies. We report a case of anti-IgLON5 disease with a multifaceted semiology and an unusually good response to glucocorticoid monotherapy. Case presentation A 68-year-old man with type 2 diabetes was evaluated for an 8-month history of progressive gait disorder causing frequent falls. He also suffered from obstructive sleep apneas and complained of dysphonia, dysarthria, occasional dysphagia, urinary incontinence, and upper limb action tremor. Neurological examination demonstrated bilateral eyelid ptosis, limitation of ocular horizontal smooth pursuit movements, slow horizontal saccades, and lack of inhibition of the vestibulo-ocular reflex during rapid horizontal head torsions. The patient also displayed involuntary, slow, rhythmic movements of the left periorbital and perioral muscles, spreading to the ipsilateral hemipalate and hemitongue, along with bilateral negative upper limb myoclonus. There were proximal muscle wasting in the upper limbs, proximal weakness of the four limbs, and diffuse fasciculations. Ataxia of stance and gait and of the four limbs was noted. MRI of the brain and spine was unremarkable; nerve conduction studies revealed a chronic, predominantly demyelinating, sensory-motor polyneuropathy, probably due to diabetes. Routine CSF examination was unrevealing and serum GFAP level was 89.6 pg/mL; however, the autoimmunity tests revealed a high-titer positivity for anti-IgLON5 autoantibodies in both CSF and serum, leading to the diagnosis of anti-IgLON5 disease. Symptoms improved significantly after intravenous methylprednisolone. Conclusions Hemifacial and hemiorolingual myorhythmia along with peculiar oculomotor abnormalities characterizes the multifaceted clinical picture of our case. The complex semiology of our patient may reflect multifocal targeting of the autoimmune process or sequential spreading of tau inclusions in different brain areas. Our patient’s optimal response to glucocorticoid monotherapy could be underpinned by a slightly different phenotype in which autoimmunity plays a greater pathogenic role than tauopathy, with a lower burden of tau deposition. In such patients, neurodegeneration and tau accumulation could be merely secondary to immune-mediated neuronal dysfunction, supporting the existence of a group of glucocorticoid-responsive patients.